(untitled) (Research, Society and Development, 2020)
Aims: To produce a yogurt with the addition of beet and unripe banana flours in order to add nutritional value and make this drink a functional food, since the supply of vitamins, minerals, and fibers can help in the prevention of non-transmissible chronic diseases (NTCDs). Methods: Microbiological, physicochemical, and sensory analyses were performed to certify its innocuousness to health, nutritional improvement, and acceptance by consumers, respectively. Results: The yogurt containing 4% of each flour presented coliforms at 45ºC within the maximum values established by the current legislation, as well as increased nutritional value, with emphasis on a 21% increase in proteins and 133% in minerals. It also had a decrease in moisture content, resulting in a longer shelf-life product. Three yogurt formulations (4%, 3%, and 2%) were prepared for the sensory analysis, which showed a preference for the formulation with the lowest concentration of beet flour (p>0.05). Concerning the purchase intention, the results indicated the tasters might buy the product if it were available on the market. Conclusion: unripe banana and beet flours behaved as promising ingredients, from a functional point of view, as they enrich yogurt with antioxidant and bioactive compounds, demonstrating the potential of this new food product in preventing oxidative damage to health.